Preliminary Study of Using KY-038 Sensor Based on Arduino UNO and LabView to Determine the Pulse Rate - Nur Afifah Zen; Slamet Indriyanto; Indah Permatasari; Juwansyah Sasmita; Lia Yuliantini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
The KY-038 sensor module is designed using Arduino UNO and LabView to allow human pulses. The experiment was carried out by making a design consisting of the KY-038 sensor module, Arduino UNO and LabView on a computer. LabView software is used to display pulse wave patterns. Measurement of the pulse will involve human objects with variations 3 namely relax (sit), sit and after running in place. The experimental results show that the different activities affect the voltage released on a chart that has a rating of 3 - 3.5 V. The more activities that are carried out before retrieving the pulse data, the greater the voltage that is read on the LabView results graph. After running in place, the value of the voltage and pulse are 3.5 V and 97 beats per minute, respectively